2021
DOI: 10.1111/hsc.13369
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐synthesis of how parents of children with autism describe their experience of accessing and using routine healthcare services for their children

Abstract: Autism spectrum disorders are characterised by deficits in social communication and interactions, as well as the presence of restricted, repetitive patterns of behaviours, interests or activities (American Psychiatric Association [APA], 2013). Children and their families living with autism face a multitude of complexities around obtaining an initial diagnosis, and in accessing appropriate, timely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…3,24 Furthermore, waiting rooms could be particularly challenging for autistic patients; thus, efforts to improve the comfort (e.g., developmentally appropriate toys/books) can improve the health care experience. 25,26 Barriers noted in other studies but not explicitly discussed by our participants included stigma and socioeconomic determinants of health. 2,9…”
Section: Discussionmentioning
confidence: 93%
“…3,24 Furthermore, waiting rooms could be particularly challenging for autistic patients; thus, efforts to improve the comfort (e.g., developmentally appropriate toys/books) can improve the health care experience. 25,26 Barriers noted in other studies but not explicitly discussed by our participants included stigma and socioeconomic determinants of health. 2,9…”
Section: Discussionmentioning
confidence: 93%
“…Even though the included studies span over 21 years (1999 to 2020), it is surprising how the results and the themes within the studies did not vary across time, setting, and location (Walsh et al, 2021;Doherty et al, 2022;Soke et al 2018;Mazurek et al, 2020;Heslop et al, 2021;Boshoff et al, 2021;Mencap, 2012). Although policies and legislatures keep changing and upgrading over time, the barriers encountered by autistic children and their parents when accessing healthcare services remain constant, which reinforces the need for the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Other, ASD and non-ASD behavioral parent treatment research has indicated that the use of motivational interviewing techniques enhances caregiver engagement and ultimately outcomes (Nock & Kazdin, 2005 ; Rogers et al, 2019 ). It is also possible that variables such as simple access to treatment with a provider with ASD knowledge and understanding, having parental voices heard and recognized, feeling listened to and validated, and hearing about the experiences of other caregivers of autistic youth are helpful (Boshoff et al, 2021 ). Thus, improvements were noted in both groups, possibly due to the PST being an efficacious intervention on its own.…”
Section: Discussionmentioning
confidence: 99%